Cognitive and emotional empathy in individuals at clinical high risk of psychosis. (12th May 2020) - Montag, C.; Brandt, L.; Lehmann, A.; De Millas, W.; Falkai, P.; Gaebel, W.; Hasan, A.; Hellmich, M.; Janssen, B.; Juckel, G.; Karow, A.; Klosterkötter, J.; et al.
Abstract : Background: Impairments of social cognition are considered core features of schizophrenia and are established predictors of social functioning. However, affective aspects of social cognition including empathy have far less been studied than its cognitive dimensions. The role of empathy in the development of schizophrenia remains largely elusive. Methods: Emotional and cognitive empathy were investigated in large sample of 120 individuals at Clinical High Risk of Psychosis (CHR‐P) and compared with 50 patients with schizophrenia and 50 healthy controls. A behavioral empathy assessment, the Multifaceted Empathy Test, was implemented, and associations of empathy with cognition, social functioning, and symptoms were determined. Results: Our findings demonstrated significant reductions of emotional empathy in individuals at CHR‐P, while cognitive empathy appeared intact. Only individuals with schizophrenia showed significantly reduced scores of cognitive empathy compared to healthy controls and individuals at CHR‐P. Individuals at CHR‐P were characterized by significantly lower scores of emotional empathy and unspecific arousal for both positive and negative affective valences compared to matched healthy controls and patients with schizophrenia. Results also indicated a correlation of lower scores of emotional empathy and arousal with higher scores of prodromal symptoms. Conclusion: Findings suggest that the tendency to 'feel with' an interaction partner is reduced in individuals at CHR‐P. Altered emotional reactivity may represent an additional, early vulnerability marker, even if cognitive mentalizing is grossly unimpaired in the prodromal stage. Different mechanisms might contribute to reductions of cognitive and emotional empathy in different stages of non‐affective psychotic disorders and should be further explored.